Brunnerian adenomatous polyp of duodenum - Marella, Muzio; Pereira, Orlando; Lareo, Cardozo; Cassinelli, Juan; Falconi, Luis (Cirugía del Uruguay, 1974)
One case of duodenal adenomatous Brünnerian polyp whose only symtomatology was pain in the right upper abdomen is reportea. The operative diagnosis was tumor in duodenal bulb. Gastropiloroduodenostomy was made with a large duodenal resection and gastro duodenal anastomose. The definitive diagnosis of the lesion was histologic. The highest degree of rarity about this sort of tumor is pointed out.